2-Mercaptobenzoxazole as a Novel Sulfur Transfer Agent in the Cu-Catalysed “On-Water” Synthesis of Symmetrical or Unsymmetrical Sulfides under Phase Transfer Catalysis Conditions - Abele, Edgars; Golomba, Lena; Abele, Ramona (Current Organic Synthesis, 2017)
Aim and Objective: In the chemical literature, there is very little data about copper catalysed synthesis of diaryl sulfides in water. In this work we present a novel highly selective Cu-catalysed “on-water” method of the synthesis of symmetrical and unsymmetrical sulfides from aryl iodides and 2-mercaptobenzoxazole as a novel sulfur transfer agent. Material and Method: 2-Mercaptobenzoxazole was presented as a novel sulfur transfer agent. Novel Cucatalysed “on-water” method for the selective synthesis of diaryl sulfides from diaryl iodides in the phase transfer catalytic system 2-mercaptobenzoxazole / CuI / proline/ KOH/ Adogen 464 was developed. Results: We have elaborated the novel catalytic system 2-mercaptobenzoxazole / KOH / CuI / Adogen464 / proline for the synthesis of diaryl sulfides from corresponding aryl iodides in water. The products were isolated in 30-76% yields. Modification of the presented method was successfully applied in the preparation of unsymmetrical sulfides. For example, benzylphenylsulfide and benzyl(3-fluorophenyl)sulfide were selectively prepared in 68% and 57% yields, correspondingly, by three-component, one-pot coupling reaction in the system PhCH2Br (1 mmol) / ArI (1 mmol) / 2-meracaptobenzoxazole (1 mmol) / CuI (20 mol.%) / proline (20 mol.%)/ Adogen464 / H2O at 160°C. Conclusion: Thus, novel Cu-catalyzed “on-water” method for the synthesis of symmetrical and unsymmetrical sulfides in the system aryl iodides (and benzyl bromide) /2-mercaptobenzoxazole / KOH / CuI / Adogen464 / proline / H2O was presented. Interestingly, similar reaction of 2-mercaptobenzothiazole in the above system led only to 2-arylsulfanylbenzothiazoles. According to our point of view, the presented method is the best for the selective preparation of sulfides possessing NH2, Br and F functional groups.
Keywords: aryl iodides